Survey of mineral oil hydrocarbons in infant formula from the Chinese market. Issue 6 (2nd June 2020) - Sui, Haixia; Gao, Hongbo; Chen, Yanfen; Ke, Runhui; Zhong, Huaining; Zhong, Qiding; Liu, Zhaoping; Song, Yan
ABSTRACT: Mineral oil hydrocarbon (MOH) contamination of various foods in the past few decades has raised much concern due to its potential adverse health effects. Since infant formulas (IF) is the major food source for infants, it is necessary to understand MOH contamination level in IF and consequent potential food safety risks. Data on the contamination of IF by mineral oil are lacking in China. On the other hand, the analysis of MOH in food is difficult. There is no harmonised standard analytical method for testing MOHs in IF. GC-FID/MS was chosen as the analytical tool being more convenient for surveys at a national level. Fifty-one IFs comprising dairy milk-based IFs (n = 39) and goat milk-based IFs (n = 12), including different stages (Stage 1, 2 and 3), package type (metal cans and paper boxes) were collected in China market in 2018 for this survey. 17 of 51 IFs were found positive, but trace levels MOAH were found (≤0.7 mg/kg). For the positive samples, all the MOSH and MOAH hump fell into the C16-C25 fraction. MOH humps were found in all the 12 goat milk-based IFs, even 4 samples are reported with quantifiable values which are higher than the method defined LOQ. The highest quantifiable MOH contamination level of goat milk-based IFs were MOSH = 3.5 mg/kg and MOAH = 0.7 mg/kg. Further root cause analysis of contamination is highly recommended to control the MOH contamination for goat milk-based IFs.